ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI PENGAMBILAN KREDIT OLEH PELAKU USAHA PROPERTY DI KOTA BATAM - Handra Tipa; Mortigor Afrizal Purba (JURNAL AKUNTANSI BARELANG, 2019)
Factors that are one aspect of the failure of property businesses in accessing Working Capital Loans and Investment Loans are misunderstandings of business actors who refer to what factors are important assessments of banks in lending. This study aims to analyze the factors that influence credit taking by property businesses in Batam City. in particular, because land ownership status in Batam is different from other regions in Indonesia. Based on data processing In partial interest rates have a significant effect on the decision to take credit by property businesses in Batam City with a significant value = 0,000 <0.05, Ha is accepted and Ho is rejected. From these calculations the interest rate has a significant effect on Credit Decisions, influential collateral significant to the decision to take credit by property business actors in Batam City with a significance = 0.017 <0.05 then Ha is accepted and Ho is rejected. From these calculations, the guarantee has a significant effect on Credit Decisions. Credit nominal has a significant effect on the decision to take credit by property businesses in Batam City with a significant value = 0,000 <0,05 so Ha is accepted and Ho is rejected. Likewise, the variable bank service has a significant effect on the decision to take credit by property businesses in Batam City. Simultaneously the influence of interest rates, guarantees, nominal credit, and bank services have a significant effect on the decision in credit disbursement for property entrepreneurs in the city of Batam. From the results of this study entrepreneurs must be wiser in making credit decisions and be better able to see better opportunities in the future so that the business undertaken can grow much more rapidly.